Spirits and skins: the sceapheord of Exeter Book Riddle 13 and holy labour - Burns, R (Oxford University Press, 2022)
While the unnamed creatures of Exeter Book Riddle 13 have been read as ‘chickens’ since the early twentieth century, this solution has never fully satisfied either the narrative description or the cryptic puzzles of this short verse text. In this article, I propose a new solution, the Old English word SCEAPHEORD (‘flock of sheep’), which fulfils the various clues of the riddle and fits more satisfactorily among the quadruped cluster of neighbouring Riddles 12, 14 and 15. Far from settling the meaning of the text, this new solution opens the riddle to a range of interpretative possibilities. Following previous critical work on the role of medieval riddles in teaching interpretative practice, I will demonstrate that the riddle invites readings of the wandering sceapheord on several discrete levels, in a process analogous to fourfold biblical exegesis: the literal (a flock of sheep), the historical (allusions to biblical Eden, following Patrick Murphy) and the anagogical (images of renewal and salvation). A fourth, moral level of interpretation is revealed through attention to the riddle’s letter-games and etymological puns, which, in the Isidorean tradition, portray human language as reflective of material reality. By emphasizing this relationship between the textual and the real, the poem encourages monks to apply their skills of exegetical analysis to their daily labour (represented by the ubiquity of sheep-rearing in the early medieval English economy). While celebrating the spiritual meaning of individual acts of manual labour, Riddle 13 also reinforces the moral and theological importance of collective monastic work.